2012
DOI: 10.1093/eurheartj/ehs073
|View full text |Cite
|
Sign up to set email alerts
|

The effects of continuous positive airway pressure therapy withdrawal on cardiac repolarization: data from a randomized controlled trial

Abstract: Continuous positive airway pressure withdrawal is associated with the prolongation of the QT(c) and TpTe(c) intervals and TpTe/QT ratio, which may provide a possible mechanistic link between OSA, cardiac dysrhythmias, and thus sudden cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 45 publications
1
38
2
1
Order By: Relevance
“…The increase in the length of these intervals was positively correlated with the change in the severity of OSA, suggesting that the risk for malignant dysrhythmias increases with the severity of OSA. In addition, there was a correlation between the change in the QTc and change in the urinary noradrenaline levels, suggesting that increased sympathetic nervous system activity may be one of the underlying mechanisms between OSA and the increased dispersion of cardiac repolarisation [89]. According to PANIKKATH et al [83] an uncorrected TpTe interval .100 ms, and a QTc interval .430 ms in the resting ECG, are associated with an increased risk of SCD.…”
Section: Interventional Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in the length of these intervals was positively correlated with the change in the severity of OSA, suggesting that the risk for malignant dysrhythmias increases with the severity of OSA. In addition, there was a correlation between the change in the QTc and change in the urinary noradrenaline levels, suggesting that increased sympathetic nervous system activity may be one of the underlying mechanisms between OSA and the increased dispersion of cardiac repolarisation [89]. According to PANIKKATH et al [83] an uncorrected TpTe interval .100 ms, and a QTc interval .430 ms in the resting ECG, are associated with an increased risk of SCD.…”
Section: Interventional Studiesmentioning
confidence: 99%
“…In a randomised-controlled trial, analysis of QTc and TpTec (TpTe corrected for heart rate) intervals from a 12-lead ECG found that CPAP withdrawal for 2 weeks was associated with both prolongation, and an increase in dispersion, of repolarisation, providing a possible mechanistic link between OSA, cardiac arrhythmias and SCD [89]. The increase in the length of these intervals was positively correlated with the change in the severity of OSA, suggesting that the risk for malignant dysrhythmias increases with the severity of OSA.…”
Section: Interventional Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…ECG was recorded with a 12-lead ECG (AT 104 PC, Schiller-Reomed AG, Switzerland) set at 25-mm/s paper speed and 10-mm/mV amplitude. Measurements of the ECG intervals were performed twice with dedicated ECG analysis software (DatInf® Measure 2.1d, DatInf GmbH, Tübingen, Germany) by two investigators who were blinded to the patient's data as previously described [23]. The mean of the ECG interval measurements by the two investigators was calculated and used for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…An analysis of the dynamics of the QT interval before and after the treatment of OSA by continuous positive airway pressure (CPAP) is given in a study by Rossi et al [28]. This study characterized the trend towards a significant QT interval elongation among patients who discontinued therapy.…”
Section: Electrical Myocardial Instabilitymentioning
confidence: 99%